2014
DOI: 10.1590/1677-3225v13n3a12
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water/powder ratio in the mineral and synthetic casts

Abstract: Aim: To evaluate the influence of varying the water/powder ratio on the compressive strength of type IV mineral and synthetic casts. Methods: Four commercial brands of type IV mineral and synthetic casts were evaluated: Durone, Herostone, Fuji Rock, and Elite Rock. Ninety-six test samples were prepared from a silicone matrix, according to ADA's standard no. 25. The samples were prepared according to the manufacturer's recommendations with a normal water/powder ratio (n = 12) and with 20% extra water (n = 12), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 17 publications
(15 reference statements)
0
10
2
Order By: Relevance
“…22 Since wet casts usually have inadequate strength and surface hardness, dentists normally must wait for 24-48 h before manipulating gypsum casts. 23 The aforementioned ratio guidelines were followed, 24 though a recent study 25 observed the influence of the variation of water/powder on the compression resistance of plaster type 4 and synthetic models and observed that an increase in water by 20% caused no significant difference in the compressive strength of the material. Polyurethane resin (NOVOX, Mangran, Curitiba, and Paraná, Brazil) was presented as a material easy to handle and to homogenize its components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Since wet casts usually have inadequate strength and surface hardness, dentists normally must wait for 24-48 h before manipulating gypsum casts. 23 The aforementioned ratio guidelines were followed, 24 though a recent study 25 observed the influence of the variation of water/powder on the compression resistance of plaster type 4 and synthetic models and observed that an increase in water by 20% caused no significant difference in the compressive strength of the material. Polyurethane resin (NOVOX, Mangran, Curitiba, and Paraná, Brazil) was presented as a material easy to handle and to homogenize its components.…”
Section: Discussionmentioning
confidence: 99%
“…Cast resistance is directly affected by two factors, water/powder ratio and mixing time. 25 The current study used a vacuum mechanical mixer (Elite Mix of Zhermack Technical Rome, Italy) considering that mechanized manipulation promoted a more homogenous mixture. According to the specifications of the ADA 26 on evaluating dimensional changes of materials used in dental model casting, the most widely used method is the measurement of the space between two lines contained in the master model.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Tavarez et al . [ 15 ] showed that a 20% increase over distilled water recommended that volume does not interfere with compression properties of a die type IV. Azer et al .…”
Section: Discussionmentioning
confidence: 99%
“…Areas of interest include improved mechanical strength such as resistance to fracture, surface hardness, and resistance to abrasion, and surface improvements such as surface rugosity, accuracy, and detail reproducibility. [ 8 10 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…Type III and IV gypsum are commonly used to fabricate casts for prosthodontics procedures, as they have acceptable mechanical properties such as high resistance, minimal setting expansion, and high surface hardness resistance [1,3,6,7]. In addition, high accuracy is also essential to accurately reproduce details and for dimensional stability [8][9][10][11][12]. The water/ powder ratio is a critical factor determining the physical and chemical properties of a cast, and any modification of this ratio may alter these properties.…”
Section: Introductionmentioning
confidence: 99%